2021
DOI: 10.1111/jfpp.15411
|View full text |Cite
|
Sign up to set email alerts
|

Heat penetration characteristics and quality of ready‐to‐eat shrimp in masala (Litopenaeusvannamei) in flexible retortable pouches

Abstract: Shrimps are the most traded commodity among the various seafood products exported from India. Though the frozen products are the major exporting items, there is ever increasing demand for valueadded products, especially in convenient ready-to-eat form. India is one of the major producers of aquacultured fish and shellfishes.Among the cultured shrimp species, Pacific white leg shrimp (Litopenaeus vannamei) has gained very quick popularity among the farmers in India owing to its fewer occurrences of diseases.Glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The proximal analyses results revealed that the protein level was altered among the raw and processed crustacean samples. A common reduction in protein level can be explained by protein denaturation based on high temperatures during thermal processes (Puthanangadi Dasan et al, 2021). Similarly, moisture and ash levels also decreased during thermal processing in both shrimp and prawn samples, which can be explained by physically removing moisture during the heat process.…”
Section: Proximate Composition and Ph Differences Among Raw And Proce...mentioning
confidence: 96%
“…The proximal analyses results revealed that the protein level was altered among the raw and processed crustacean samples. A common reduction in protein level can be explained by protein denaturation based on high temperatures during thermal processes (Puthanangadi Dasan et al, 2021). Similarly, moisture and ash levels also decreased during thermal processing in both shrimp and prawn samples, which can be explained by physically removing moisture during the heat process.…”
Section: Proximate Composition and Ph Differences Among Raw And Proce...mentioning
confidence: 96%